Integrating 21st Century Skills Into Islamic Religious Education: A Holistic Value -Based Framework - Cukup Islamiarso; Lia Laili Rosadah; Muhammad Sirozi (IJGIE (International Journal of Graduate of Islamic Education), 2026)
The rapid development of globalization, digital technology, and socio-cultural transformation has created significant challenges for contemporary education systems, including Islamic Religious Education (IRE). These changes require educational institutions to equip students with competencies that extend beyond traditional knowledge acquisition. This study aims to examine the integration of twenty-first century skills within the curriculum of Islamic Religious Education and to analyze its contribution to enhancing students’ competencies in modern educational contexts. This research employs a qualitative approach using a systematic literature review of relevant national and international sources, including academic books, peer-reviewed journal articles, and policy documents. The data were analyzed through thematic content analysis to identify key patterns related to the urgency, pedagogical strategies, benefits, and challenges of integrating twenty-first century skills in IRE. The findings reveal that competencies such as critical thinking, creativity, collaboration, communication, digital literacy, and global citizenship awareness play a crucial role in strengthening the relevance of Islamic Religious Education. Their integration supports a shift from content-oriented instruction toward a more holistic educational approach that combines cognitive development with ethical awareness and social responsibility. However, the study also identifies several structural and pedagogical challenges, including limited teacher readiness, inadequate technological infrastructure, and curriculum rigidity. The study offers important educational implications by proposing an integrative and value-based framework that aligns twenty-first century competencies with Islamic pedagogical principles. This framework provides guidance for curriculum development, instructional design, and teacher professional development in Islamic Religious Education. Future research is recommended to conduct empirical and comparative studies to examine the effectiveness and measurable impact of such integration across diverse educational contexts.